Variability and genetic associations of pigeon pea yield traits in Mozambique - Pedro, César; Cruz, Cosme Damião; Donça, Marques Cachisso Bambo; Somueque, Salva Inácio; Gimo, Sabir Tualibo; Silva, Michele Jorge da; Ferraz, Alexandre Gomes; Rosado, Renato Domiciano Silva; Bhering, Leonardo Lopes (Pesquisa Agropecuaria Brasileira, 2022)
The objective of this work was to evaluate the genetic variability and associations of yield traits of pigeon pea, for indication of this crop for the breeding program in Mozambique. Eleven pigeon pea traits were evaluated in a experimental design with three randomized complete blocks, in the environments of Namapa (I) and Montepuez (II), in 2017/2018. To evaluate the traits, analyses of variance, genetic parameters, correlations, correlation network, and path analysis were used. In both environments, there is a high genetic and phenotypic variability for primary branches, secondary branches, pods per plant, number of seed per pod, pod width, pod length, and yield, as well as a high heritability for all traits except for plant height. The primary and secondary branches have a high correlation with yield and a positive direct effect on it. However, plant height and pods per plant show a high phenotypic variability and a positive correlation with yield in environment I. Pods per plant, weight of 100 seed, and primary branches show high direct positive effects in environment I, and secondary branches and number of seed per pod, in environment II. The primary and secondary branches show high variability and associations with yield in both environments and are indicated for the pigeon pea breeding program in Mozambique.
Keywords: Cajanus cajan; correlation; genetic parameters; path analysis